Electronic safety-netting tool features considered important by UK general practice staff: an interview and Delphi consensus study - Claire Friedemann Smith; Sue Duncombe; Susannah Fleming; Yasemin Hirst; Georgia Bell Black; Clare Bankhead; Brian D Nicholson (BJGP Open, 2023)
Background: The potential of the electronic health record to support safety netting has been recognised and a number of electronic safety-netting (E-SN) tools developed. Aim: To establish the most important features of E-SN tools. Design & setting: User-experience interviews followed by a Delphi study in a primary care setting in the UK. Method: The user-experience interviews were carried out remotely with primary care staff who had trialled the EMIS E-SN toolkit for suspected cancer. An electronic modified Delphi approach was used, with primary care staff involved in safety netting in any capacity, to measure consensus on tool features. Results: Thirteen user-experience interviews were carried out and features of E-SN tools seen as important formed the majority of the features included in the Delphi study. Three rounds of Delphi survey were administered. Sixteen responders (64%) completed all three rounds, and 28 out of 44 (64%) features reached consensus. Primary care staff preferred tools that were general in scope. Conclusion: Primary care staff indicated that tools that were not specific to cancer or any other disease, and had features that promoted their flexible, efficient, and integrated use, were important. However, when the important features were discussed with the patient and public involvement (PPI) group, they expressed disappointment that features they believed would make E-SN tools robust and provide a safety net that is difficult to fall through did not reach consensus. The successful adoption of E-SN tools will rely on an evidence base of their effectiveness. Efforts should be made to assess the impact of these tools on patient outcomes.